Meningkatkan Hasil Belajar PAKBP Dengan Metode PBL Materi Mengembangkan Kemampuan Diriku Fase B Kelas IV SD Negeri 20 Simbolon Purba Tahun Pelajaran 2024/2025 - Lismawaty Margareta Munte; Fr.Wuriningsih; Budi Hartono (Sekolah Tinggi Pastoral Kateketik (STPKat) Santo Fransiskus Assisi Semarang, 2024)
Religious education is an important component in the Indonesian national education system, which functions to shape the personality of students so that they are not only knowledgeable, but also have noble character. Based on the results of observations made by researchers at SD Negeri 20 Simbolon Purba, Palipi District Samosir Regency, researchers found several problems related to Catholic religious learning, namely limited teaching resources, lack of relevant materials and textbooks, lack of integration of religious values ​​in daily life, less relevant approaches to learning methods and models, the aim of this research is to determine the increase in learning outcomes by PBL method and increasing learning achievement targets for class IV students at SD Negeri 20 Samosir Purba, this research uses Classroom Action Research (PTK) with the Problem Based Learning (PBL) Model in this research has been carried out in two cycles, this is proven by the increase in participant scores post test students can be can be seen from the details of the achievements of each cycle, namely in Cycle I New Developing 0 People = 0%, Adequate = 6 People = 75%, Proficient = 1 Person = 12.5%, Proficient = 1 Person = 12.5%. Meanwhile in Cycle II New Developing = 0 people = 0 %, Decent = 1 person = 12.5 %, Capable = 4 people = 50 %, Proficient = 4 people = 50 %, and the average value shows an increase from a score of 71, 25 eligible categories become 85 with the advanced category